PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS MACROMEDIA FLASH 8 UNTUK MENINGKATKAN MOTIVASI BELAJAR PADA PEMBELAJARAN IPA KELAS V SDN SINDANGJAYA 04 - Khairani Ausyifa Rahmah; Awalina Barokah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research titled "Development of Interactive Learning Media Based on Macromedia Flash 8 to Enhance Learning Motivation in Science Education for Grade 5 Students at SDN Sindangjaya 04" aims to develop and evaluate the effectiveness of interactive learning media based on Macromedia Flash 8 in enhancing the learning motivation of Grade 5 students at SDN Sindangjaya 04, specifically in the subject of Science. The research employs the Research and Development (R&D) method by applying the ADDIE model as a framework for developing the learning media. The results of the study show that the developed media is proven to be effective in increasing students' learning motivation, particularly in Science, as indicated by the effectiveness survey results, with a percentage of 89.56%. The conclusion of this research is that interactive learning media based on Macromedia Flash 8 is feasible and effective for use in the learning process and can enhance students' learning motivation.